(untitled) (Jurnal Teknologi Industri Pertanian, 2017)
This research was aimed to investigate the ability of porang (Amorphophallus oncophyllus) flour to stabilizeoil-in-water (O/W) emulsion and further more can be used as encapsulating matrix for fish oil microencapsules. The experiments were divided into three stages: A) emulsification with ultra turrax to form coarse emulsion which designed using randomized block design with two variables, namely concentration of porang flour (55% glucomanan) i.e. 0.5% and 1% , and oil concentrations i.e.20%, 30% and 40%;B) Variables that produced stable coarse emulsions were selected to be used in fine emulsion process using high pressure homogenizer; and 3) Stable and effective fine emulsions were spray dried to produce fish oil microcapsules. Porang flour used was yellow in colour with 7.75% moisture content, 8% ash, 9.72% crude fiber, 0.43% fat and 55% glucomanan. The statistical analysis showed that all variables i.e. porang flour and oil concentrations influenced the emulsifying activity values and viscosity significantly (P≤0.01). The most stable coarse emulsion was the one that emulsified by 40% oil and 1% porang flour with viscosity of 3647 cP and 100% emulsifying activity, and separation of 2.70 ml serum layer after 7 days storage. Stable fine emulsion was produced by the same variables’ combination as coarse emulsion with average droplet size of 614 nm, polydispersity index of 0.237, emulsion zeta potential of -25.83 mV, and separation of only 0.25 mL after 16 days storage. Emulsion that spray dried effectively contained 0.5% porang flour. The peroxide values of fish oil microcapsules were in the range of 16.5 – 32.5 meq/kg oil. Keywords: porang flour, glucomannan, o/w emulsion, emulsion stability, stabilizer